Identification of Belat Bycatch in Anak Setatah Village Rangsang Barat District Meranti Island Regency Riau Province - Sembiring, Firma Surmana; Brown, Arthur; Yani, Alit Hindri (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
The belat is a passive fishing gear that belongs to a group of traps operated in areas around the coast. In its operation, the belat not only produces the main catch but also gets bycatch. This study aims to identify the main catch and by catch. The research method used is the survey method by making direct observations of the belat catch and then the catch is identified as the type of fish, the number of individuals, and the weight of the fish. The results of descriptive analysis showed that the main catches were two types of shrimp, namely white shrimp (Penaeus indicus) and striped shrimp (Penaeus monodon) with a weight of 30400 g. The main catches were white shrimp (Penaeus indicus) and striped shrimp (Penaeus monodon). The by-catches were small fish and young fish, the by-catches consisted of 6 species with a total weight of 29300 g